A Commander Kılled By Peg: the Depıctıons of Jael And Sysera In Baroque Paıntıng at Torah Iconography - Tercanlı, Akın (Fırat University, 2023)
According to the iconography, after the death of Ehut, the savior and guide, the Israelites did what was evil in the eyes of the Lord. The Lord then delivers Israel into the hands of King Yavin, the Canaanite king of Hasor. King Jabin, who had nine hundred iron chariots, ruled oppressively in the land for twenty years with the help of a powerful commander named Sisera. While all this was happening, Israel was ruled by Deborah the Prophetess, the wife of Lappidoth. One day the prophetess Deborah receives a message from the Lord. According to this information, Sisera, the King’s favorite man and commander, will be killed by a woman. Learning of this, the female ruler informs her commander named Barak. The forces led by Barak and Sisera’s soldiers clashed on Mount Tavor. Sisera, whose entire army was slaughtered by the forces under the command of Barak, barely escaped with his life. Fleeing on foot, the commander took refuge in the tent of Yael, the wife of Hever, one of the Kenites. The reason why the commander took refuge here was that Yavin and Hever were on good terms. Yael accepts Sisera into her tent and makes the necessary preparations for him to rest. While the commander is asleep, Jael quietly enters the tent and takes action to fulfill the prophecy foretold to Deborah. With a mallet and an iron stake, she nails Sisera to the ground by the temple and the commander dies instantly. After this cold-blooded act, Yael goes out to meet the commander Barak to show him Sisera’s corpse. Watching her, Barak sees Sisera’s dead body with a stake through his temple. With the death of the commander, King Yavin’s power gradually diminishes and, led by Deborah, the Canaanite King Yavin is eliminated. In this study, we have focused on some paintings based on the iconography of Yael and Sisera. Considering both the stylistic characteristics and the periods of creation of the paintings of Jacopo Vignali (1592-1664), Mateo Gallardo Solier (1600-1667) and Felice Ficherelli (1603-1660), which we included in the study, it has been determined that these paintings created by the artists have Baroque characteristics. The Baroque style is generally known as a style that profoundly influenced 17th century European art with its focus on depicting a fluid moment, diagonal expression in composition, theatrical depiction, contrast relationship between light and dark surfaces, use of light, voluminous fabric structures, atmospheric themes, dark colored background and depiction understanding that does not fit into the frame. The basic dynamics of the style in Baroque painting can be seen more clearly in the close relationship between the depictions and iconography. This approach, that is, the relationship between artwork and iconography, has turned into an orientation that directly influenced 17th century Europe, where the depictions we examined were created. The tradition of depiction based on the life stories of religious or historical characters mentioned in the Old and New Testaments is presented to the viewer more clearly, especially in atrocity paintings. In addition to leaving a spiritual impact on the viewer, the implicit image in the depictions also aims to reflect the oppression of the authority on large masses of people through visual data. It is possible to see the influence of such an understanding in two paintings that are dated to the second half of the 17th century due to their stylistic characteristics, in addition to one work with a known date (1631). We analyzed the paintings in this study according to Panofsky’s methodology. According to this method, a work of art should be analyzed under three headings: Natural (Factual and Expressive), Iconographic and Iconological Meaning. In the study, we first analyzed the paintings on the basis of Natural Meaning, which we can conceptualize as “its apparent expression.” At the conceptual level, after introducing only the basic elements visible in the painting without any additions, we moved on to Iconographic Meaning. Under this heading, we discussed the determination of the iconography that led to the formation of the relevant scenes, the relationship of the artists with the text or the aspects that differ from the passages. In Iconological Meaning, we first gave information about the artists. In the third step of the method, we discussed the stylistic characteristics of these artists, their similarities or differences, and the effects of the Baroque style on the paintings. The main purpose of our article is to determine the place of the depictions in European depiction arts by determining the originality of the paintings we examined with a methodological approach.

İkonografideki bilgilere göre kurtarıcı ve yol gösterici olarak kabul edilen Ehut’un ölümünden sonra İsrailliler, Rab’bin gözünde kötü olanı yaparlar. Rab’da bunun üzerine İsrail halkını Hasor’da egemenlik süren Kenanlı Kral Yavin’in eline teslim eder. Dokuz yüz demir savaş arabasına sahip olan Kral Yavin, bulunduğu topraklarda yirmi yıl kadar Sisera adındaki güçlü bir komutanın da yardımıyla baskıcı bir yönetim anlayışıyla hüküm sürere. Bütün bunlar yaşanırken İsrail’i Lappidot’un karısı Peygamber Debora yönetmektedir. Peygamber Debora’ya bir gün Rab tarafından bir bilgi gelir. Bu bilgiye göre Kral’ın has adamı ve komutanı Sisera, bir kadın tarafından öldürülecektir. Bunu öğrenen kadın hükümdar, durumu Barak adındaki komutanına iletir. Barak’ın öncülüğündeki kuvvetler ile Sisera’nın askerleri Tavor dağında çarpışlar. Bütün ordusu Barak komutasındaki kuvvetler tarafından kılıçtan geçirilen Sisera, çarpışmadan canını zor kurtararak kaçmıştır. Yaya olarak kaçan komutan, Kenliler’den Hever’in karısı Yael’in çadırına sığınır. Komutanın buraya sığınma sebebi Yavin ile Hever’in arasının iyi olmasıdır. Sisera’yı çadırına kabul eden Yavel, onun dinlenmesi için gerekli hazırlıkları yapar. Komutan uyuduğu bir sırada sessizce çadıra giren Yael, Deborah’a bildirilen kehaneti gerçekleştirmek üzere eyleme geçer. Eline aldığı tokmak ve demir bir kazıkla, Sisera’yı şakağından yere çiviler ve komutan orada anında can verir. Soğukkanlılıkla yaptığı bu eylemin ardından Yael, Sisera’nın cesedini göstermek üzere komutan Barak’ı karşılamaya çıkar. Kadını izleyen Barak, şakağına kazık saplanmış Sisera’nın ölü bedenini görür. Komutanın ölümüyle Kral Yavin’in gücü zamanla azalır ve Debora’nın öncülüğünde Kenanlı Kral Yavin ortadan kaldırılır. Biz de bu çalışmamızda Yael ve Sisera ikonografisi temel alınarak hazırlanmış bazı resimlere odaklandık. Çalışmaya dâhil ettiğimiz Jacopo Vignali (1592-1664), Mateo Gallardo Solier (1600-1667) ve Felice Ficherelli’nin (1603-1660) gerek üslup özelliği gerekse tasvirlerini oluşturma dönemleri dikkate alındığında sanatçılar tarafından meydana getirilen bu resimlerin Barok özellikler taşıdıkları tespit edilmiştir. Barok üslup genel olarak akışkan bir anının betimlenilmesine odaklanılması, kompozisyondaki diyagonal anlatım, teatral betimleme anlayışı, aydınlık ve karanlık yüzeyler arasındaki kontrast ilişki, ışığın kullanımı, hacimli kumaş yapıları, atmosferik temalar, koyu renkli fon ve çerçeveye sığmayan tasvir anlayışıyla 17. yüzyıl Avrupa sanatını derinden etkileyen bir üslup olarak bilinmektedir. Barok resim sanatındaki üslubun temel dinamikleri, tasvirlerin ikonografiyle kurduğu yakın ilişkide daha net bir biçimde görülür. Bu yaklaşım yani eser-ikonografi ilişkisi, incelediğimiz tasvirlerin meydana getirildiği 17. yüzyıl Avrupası’na da doğrudan etki eden bir yönelime dönüşmüştür. Eski ve Yeni Ahit’te bahsi geçen dini ya da tarihi karakterlerin hayat hikâyelerine dayanan tasvir geleneği özellikle vahşet resimlerinde daha net bir şekilde izleyiciyle sunulmuştur. İzleyicide ruhsal bir etki bırakmasının yanı sıra tasvirlerdeki örtük imaj, otoritenin geniş halk kitlelerindeki baskı unsurunu görsel veriler üzerinden yansıtmayı da amaçlamaktadır. Tarihi kesin olarak bilinen (1631) bir eser yanında üslup özelliklerinden dolayı 17. yüzyılın ikinci yarısına tarihlenen iki resimde de böyle bir anlayışın etkisini görmek olanaklıdır. Araştırmada ele aldığımız tabloları Panofsky metodolojisine göre inceledik. Bu metoda göre bir sanat eseri Doğal (Olgusal ve İfadesel), İkonografik ve İkonolojik Anlam olmak üzere üç başlık altında incelenmelidir. Çalışmada, ilk olarak “görünen ifadesi” olarak kavramsallaştırabileceğimiz Doğal Anlam üzerinden resimleri analiz ettik. Kavramsal düzeyde, ekleme yapılmadan, sadece resimde görünen temel unsurların tanıtılmasının ardından İkonografik Anlam bölümüne geçtik. Bu başlık altında, ilgili sahnelerin oluşumuna kaynaklık eden ikonografinin tespiti, sanatçıların metinle olan ilişkileri ya da pasajlardan ayrılan yönlerini tartıştık. İkonolojik Anlam’da ilk olarak sanatçılar hakkında bilgi verdik. Bahsi geçen sanatçıların üslup özellikleri, birbirlerine benzeyen ya da ayrışan noktaları ile Barok üslubun tablolar nezdindeki etkilerini de metodun üçüncü basamağında tartıştık. Metodolojik bir yaklaşımla incelediğimiz resimlerin özgünlüğü saptayarak, betimlemelerin Avrupa Tasvir Sanatları’ndaki yerinin belirlenmesi makalemizin temel amacını oluşturmaktadır.
Demirkazık ile Öldürülen Bir Komutan: Tevrat İkonografisine Göre Barok Resim Sanatı’nda Jael ve Sisera Tasvirleri
Keywords: Religious Studies; Din Araştırmaları